SEPARATION OF SOLID POLLUTANTS IN A NON-CONVENTIONAL CYCLONE DESIGN CONCEPT - PLANDOROVÁ, Katarína; KRUŽLIAK, Ondrej (Trends in education, 2009)
The present contribution provides a comparison of two design concepts of cyclones for separation of solid pollutants in ventilation systems. The author describes the principle of separation of solid pollutants at the new designed with specification of its main advantages and the possibility of its installations to plants. Students deal with the problem of design concept of cyclone separators also in the subject: Technology of Air Protection.
Keywords: separation; cyclone; cyclone design concept.